Processing of the 3C/D Region of the Deformed Wing Virus (DWV) - Reuscher, Carina Maria; Barth, Sandra; Gockel, Fiona; Netsch, Anette; Seitz, Kerstin; Rümenapf, Till; Lamp, Benjamin; Justus Liebig University Giessen (My University, 2023)
The deformed wing virus (DWV) belongs to the genus Iflavirus and the family Iflaviridae within the order Picornavirales. It is an important pathogen of the Western honey bee, Apis mellifera, causing major losses among honey bee colonies in association with the ectoparasitic mite Varroa destructor. Although DWV is one of the best-studied insect viruses, the mechanisms of viral replication and polyprotein processing have been poorly studied in the past. We investigated the processing of the protease-polymerase region at the C-terminus of the polyprotein in more detail using recombinant expression, novel serological reagents, and virus clone mutagenesis. Edman degradation of purified maturated polypeptides uncovered the C- and N-termini of the mature 3C-like (3CL) protease and RNA-dependent RNA polymerase (3DL, RdRp), respectively. Autocatalytic processing of the recombinant DWV 3CL protease occurred at P1 Q2118 and P1′ G2119 (KPQ/GST) as well as P1 Q2393 and P1′ S2394 (HAQ/SPS) cleavage sites. New monoclonal antibodies (Mab) detected the mature 3CL protease with an apparent molecular mass of 32 kDa, mature 3DL with an apparent molecular mass of 55 kDa as well as a dominant 3CDL precursor of 90 kDa in DWV infected honey bee pupae. The observed pattern corresponds well to data obtained via recombinant expression and N-terminal sequencing. Finally, we were able to show that 3CL protease activity and availability of the specific protease cleavage sites are essential for viral replication, protein synthesis, and establishment of infection using our molecular clone of DWV-A.
Keywords: ddc:630